Characterization and CNS Depressant Studies on Complexes of Mn(II), Co(II) and Ni(II) with 2-(Thiophene-2-Formylimino)Benzimidazole - Jose, C.V.; Joy Anto, T. (Asian Journal of Chemistry, 2010)
Complexes of Mn(II), Co(II) and Ni(II) with 2-(thiophene-2-formylimino)benzimidazole have been synthesized. The characterization have been done on the basis of elemental analysis, conductivity measurements, magnetic studies, IR and electronic spectral studies. Complexes have been found psychopharmacologically more effective in taming, hypnotic activities and possess much higher toxicity as compared to the ligand. Complexes with distorted octahedral geometry with ML2X2 stoichiometries have been reported (where X = Cl–, NO3–, CH3COO– and C6H5COO–).